Dynamics of Post-Flowering Nitrogen Uptake and Nitrogen Recovery Efficiency Using 15N Isotope Labeling in Corn - J. A. Fernandez; J. B. Nippert; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2020)
In corn (Zea maysL.), breeding and selection for grain yield over time has been accompanied by a simultaneous increase in plant nitrogen (N) uptake. The understanding of plant N dynamics has attracted attention due to the environmental concerns related to N losses coming from fertilization. This research study was implemented to 1) describe N uptake and allocation dynamics, and 2) quantify fertilizer recovery efficiency across late-N strategies. Two field experiments (one under irrigation and one rainfed) were conducted at the Ashland Bottoms Research Farm, KS, during 2017. Three hybrids with different year of release and three N scenarios were tested. Isotope15N was utilized as tracer to determine15N recovery and N fate within plant organs when both timings of late-N were evaluated. As15N fertilizer was applied later in the season, lower recovery of the fertilizer was achieved and proportionally more N was allocated to the developing grains. These findings can motivate future investigations using15N labelling technique to evaluate fertilizer recovery efficiency in corn.
Keywords: maize; nitrogen uptake; post-flowering; fertilizer recovery efficiency; corn